2003
DOI: 10.1101/gad.1135703
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of sex-limitation (Rsl) encodes a pair of KRAB zinc-finger genes that control sexually dimorphic liver gene expression

Abstract: Sexually dimorphic expression of a broad array of liver proteins involved in reproduction and xenobiotic metabolism is induced at puberty by sex-specific growth hormone patterns. An additional control of sex-dependent gene expression is conferred by Regulator of sex-limitation (Rsl) alleles. In variant rsl mice, females inappropriately express the male Sex-limited protein, Slp. We recently showed that a panel of male-specific liver genes is repressed by Rsl, accentuating sex differences in a hormone-independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 48 publications
(58 reference statements)
2
89
0
Order By: Relevance
“…Other hepatic transcription factors potentially involved in sex-specific expression of P450s include rsl (Krebs et al, 2003), HNF-1α (Cheung et al, 2003), HNF-4α (Wiwi et al, 2004), and RXRα (Cai et al, 2003). Sexually dimorphic P450s include CYP2C11, 2A2, 3A2, and 4A2, which are considered male-specific or malepredominant in the rat, while Cyp2d9 and 4a12 are well-characterized male-predominant P450s in the mouse.…”
Section: Introductionmentioning
confidence: 99%
“…Other hepatic transcription factors potentially involved in sex-specific expression of P450s include rsl (Krebs et al, 2003), HNF-1α (Cheung et al, 2003), HNF-4α (Wiwi et al, 2004), and RXRα (Cai et al, 2003). Sexually dimorphic P450s include CYP2C11, 2A2, 3A2, and 4A2, which are considered male-specific or malepredominant in the rat, while Cyp2d9 and 4a12 are well-characterized male-predominant P450s in the mouse.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first descriptions of such divergence relates to the differential expression of cytochrome P450 isoforms in the liver, which directly affects the rate of drug clearance [12]. Although some of these differences can be attributed to sex hormones, other stimuli are involved as well, including the gender difference in the rate and frequency of release of growth hormone, which in turn affects specific transcription factors [13], or hormone-independent transcription factors, such as Rsl [14]. Another example includes the kidney, which is more sensitive to disease and graft rejection in men than women [15].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Restoration of full wild-type Rsl function requires both Rsl1 and Rsl2, as Krebs et al (2003) demonstrated by creating transgenic rsl mice carrying BAC clones containing either Rsl1 or Rsl2. These studies led to the unexpected discovery that Rsl1 and Rsl2 play distinct roles, with each gene apparently repressing a subset of malespecific liver genes: Rsl1 represses expression of Slp and Cyp2d9, whereas Rsl2 represses Mup gene expression.…”
Section: Cloning Of Rsl1 and Rsl2mentioning
confidence: 99%
“…Compounding the cloning effort undertaken by Krebs et al (2003) was the presence in the 1-Mb Rsl locus of 23 closely related genes encoding KRAB zinc finger proteins. Nonetheless, after refining the map position to an ∼ 200-kB region containing eight KRAB zinc finger genes, two of the genes, initially termed Rslcan for Rsl candidate, were shown by Krebs et al (2003) to harbor mutations in rsl mice.…”
Section: Cloning Of Rsl1 and Rsl2mentioning
confidence: 99%
See 1 more Smart Citation